Sistem Pendukung Keputusan Rekruitmen Tenaga Kerja Mandiri Menerapkan Metode OCRA - Lumban Batu, Wahyu Harry Bai; Mesran, M; Aripin, Soeb (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Independent labor in general is an important part of supporting the running of a business for entrepreneurship. Planning for manpower needs is part of the preparation of a recruitment program to make choices to attract qualified workers to an agency. However, not all selection processes have succeeded in attracting qualified workers as desired. Therefore, the role of DSS in solving this problem is urgently needed. In this study, the results of the OCRA method, the best alternative, namely A9 for Irna Yuni, S.Sos achieved a score of 0,552.